2018
DOI: 10.4049/jimmunol.1700737
|View full text |Cite
|
Sign up to set email alerts
|

Human M2 Macrophages Limit NK Cell Effector Functions through Secretion of TGF-β and Engagement of CD85j

Abstract: NK cells play important roles during immunosurveillance against tumors and viruses as they trigger cytotoxicity against susceptible cells and secrete proinflammatory cytokines such as IFN-γ. In addition, upon activation, macrophages can become proinflammatory (M1) or anti-inflammatory (M2) cells. Although the consequences of the cross-talk between M1 and NK cells are known, the outcome of the cross-talk between M2 and NK cells remains ill-defined. Therefore, in the current work, we investigated the outcome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Anti‐inflammatory cytokines such as TGF‐β also induce NGF expression in human osteoarthritic chondrocytes . M1 macrophages produce proinflammatory cytokines such as TNF‐α and IL‐1β , while M2 macrophages produce anti‐inflammatory cytokines such as IL‐10 and TGF‐β . This piece of evidence suggests that M1‐ and M2‐derived cytokines may play a role in NGF production in IVDs.…”
mentioning
confidence: 94%
“…Anti‐inflammatory cytokines such as TGF‐β also induce NGF expression in human osteoarthritic chondrocytes . M1 macrophages produce proinflammatory cytokines such as TNF‐α and IL‐1β , while M2 macrophages produce anti‐inflammatory cytokines such as IL‐10 and TGF‐β . This piece of evidence suggests that M1‐ and M2‐derived cytokines may play a role in NGF production in IVDs.…”
mentioning
confidence: 94%
“…Comparing between MNC trioculture treated with TIMP‐1 neutralizing antibody and trioculture treated with immunoglobulin G (IgG) isotype control, no difference in CML survival was observed. Because it has been suggested that Mϕ suppresses NK activity via TGFβ, we also treated MNC trioculture with TGFβ neutralizing antibody, which showed an observable but insignificant decrease in CML survival compared with IgG isotype control‐treated trioculture (Supplementary figure 16b, gray bars). Taken together, the data suggest that the maintenance of NK mCD16 level is independent of TGFβ and Mϕ TIMP‐1 modulation of MMP–sheddase activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that the Mϕ‐protective effect was contact dependent, suggesting the plausible involvement of membrane‐bound factors on Mϕ in the modulation of NK cytotoxicity and Mϕ‐protective effect on CML. It was reported that Mϕ suppressed NK activity through ligand–receptor interactions via HLAG‐ILT2 and CD48‐2B4, but whether these interactions influence the level of NK mCD16 remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that macrophages can be classified as proinflammatory (M1) or anti‐inflammatory (M2). M2 macrophages express higher levels of HLA‐G than M1 macrophages, resulting in increased LILRB1 expression on NK cells . However, there are no significant differences in LILRB1 expression between M2‐ and M1‐like tumour‐associated macrophages.…”
Section: Lilrb1 Expression On Myeloid Cellsmentioning
confidence: 95%